Sustainability Reporting And Organizational Change: A Case Study Of A Malaysian Public Listed Company - Yusoff, Ruslaina (2014)
This study aims to understand how sustainability reporting practices (the process of developing the reporting and sustainability reporting) might influence changes in a public listed company, known as Star Berhad. An interpretive case study method is used whereby data is gathered through semi-structured interviews, document reviews, informal conversation and observations. An analysis of the annual reports for the period of eleven (11) years showed that the amount and quality of reporting in the company has increased from year to year. A significant change in reporting occurred in 2007 when the company switched to sustainability reporting from corporate social responsibility (CSR) reporting. During that year, the company introduced their sustainability framework and published it to the public. Pressures from various external stakeholders such as NGOs, competitors, buyers and shareholders, influenced the company to engage in sustainability practices and, most importantly, to communicate the comprehensive sustainability information to the public effective 2007.